Gene expression profiles of mouse spermatogenesis during recovery from irradiation - Skakkebæk Niels E; Kobayashi Shinichi; Iwamoto Teruaki; Nielsen John E; Tanaka Masami; Shah Fozia J; Leffers Henrik; Almstrup Kristian (BMC, 2009)
Abstract Background Irradiation or chemotherapy that suspend normal spermatogenesis is commonly used to treat various cancers. Fortunately, spermatogenesis in many cases can be restored after such treatments but knowledge is limited about the re-initiation process. Earlier studies have described the cellular changes that happen during recovery from irradiation by means of histology. We have earlier generated gene expression profiles during induction of spermatogenesis in mouse postnatal developing testes and found a correlation between profiles and the expressing cell types. The aim of the present work was to utilize the link between expression profile and cell types to follow the cellular changes that occur during post-irradiation recovery of spermatogenesis in order to describe recovery by means of gene expression. Methods Adult mouse testes were subjected to irradiation with 1 Gy or a fractionated radiation of two times 1 Gy. Testes were sampled every third or fourth day to follow the recovery of spermatogenesis and gene expression profiles generated by means of differential display RT-PCR. In situ hybridization was in addition performed to verify cell-type specific gene expression patterns. Results Irradiation of mice testis created a gap in spermatogenesis, which was initiated by loss of A1 to B-spermatogonia and lasted for approximately 10 days. Irradiation with 2 times 1 Gy showed a more pronounced effect on germ cell elimination than with 1 Gy, but spermatogenesis was in both cases completely reconstituted 42 days after irradiation. Comparison of expression profiles indicated that the cellular reconstitution appeared equivalent to what is observed during induction of normal spermatogenesis. Conclusion The data indicates that recovery of spermatogenesis can be monitored by means of gene expression, which could aid in designing radiation treatment regimes for cancer patients leading to better restoration of spermatogenesis.